Association of diabetes in pregnancy with child weight at birth, age 12 months and 5 years--a population-based electronic cohort study. - Kelly Morgan; Mohammed Rahman; Mark Atkinson; Shang-Ming Zhou; Rebecca Hill; Ashrafunnesa Khanom; Shantini Paranjothy; Sinead Brophy (PLoS ONE)
Background This study examines the effect of diabetes in pregnancy on offspring weight at birth and ages 1 and 5 years. Methods A population-based electronic cohort study using routinely collected linked healthcare data. Electronic medical records provided maternal diabetes status and offspring weight at birth and ages 1 and 5 years (n = 147,773 mother child pairs). Logistic regression models were used to obtain odds ratios to describe the association between maternal diabetes status and offspring size, adjusted for maternal pre-pregnancy weight, age and smoking status. Findings We identified 1,250 (0.9%) pregnancies with existing diabetes (27.8% with type 1 diabetes), 1,358 with gestational diabetes (0.9%) and 635 (0.4%) who developed diabetes post-pregnancy. Children whose mothers had existing diabetes were less likely to be large at 12 months (OR: 0.7 (95%CI: 0.6, 0.8)) than those without diabetes. Maternal diabetes was associated with high weight at age 5 years in children whose mothers had a high pre-pregnancy weight tertile (gestational diabetes, (OR:2.1 (95%CI:1.25-3.6)), existing diabetes (OR:1.3 (95%CI:1.0 to 1.6)). Conclusion The prevention of childhood obesity should focus on mothers with diabetes with a high maternal pre-pregnancy weight. We found little evidence that diabetes in pregnancy leads to long term obesity 'programming'.